Handbook of development economics - Arrow, Kenneth J (Ed.); Intriligatior, Michael D (Amsterdam Elsevier Science, 1998)
The handbook of development economics is in three volumes.the first volumes contents are-Economic development,structural economics development,and human resources and labour markets.The volumes two contents are-Planning and resouce allocation,internationa
Keywords: ECONOMIC DEVELOPMENT-HANDBOOK; MANUAL; DEVELOPMENT ECONOMIC